PENERAPAN TERAPI REALITA UNTUK MENGATASI KENAKALANREMAJA PADA SISWA BROKEN HOME - Suci Amaliya Fradinata; Netrawati; Yeni Karneli (CV Putra Publisher, 2023)
We still encounter many students at school who often commit acts that violate school rules, in other words, there are juvenile delinquents. The existence of juvenile delinquency behavior needs to get special attention and approach. In this paper the author offers an approach or reality counseling to overcome the phenomenon of juvenile delinquency in students due to broken homes. The purpose of this counseling practice is to find out the efforts and success in dealing with broken home juvenile delinquency through reality counseling. The method used is a literature review or also called a literature review where a study makes descriptions of reading sources, be it books, journals, articles, and magazines. Literature review or called a literature review or literature review, a literature review is a description or description of literature that is relevant to a particular field or topic. The findings of this research are the counselor invites the counselee to understand and make the counselee aware that the condition of a broken home does not always have to be used as an excuse for the counselee to commit acts of delinquency as a way of fulfilling their basic needs. Reality counseling helps counselees face reality and meet basic needs without harming themselves or others. The counselee is invited to act realistically according to the fact that he is in a family environment that is not conducive to meeting his needs.